2016
DOI: 10.1111/jcmm.12856
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Silencing of Prrx1b suppresses cellular proliferation, migration, invasion and epithelial–mesenchymal transition in triple‐negative breast cancer

Abstract: Triple-negative breast cancer (TNBC) is a highly aggressive tumour subtype associated with poor prognosis. The mechanisms involved in TNBC progression remains largely unknown. To date, there are no effective therapeutic targets for this tumour subtype. Paired-related homeobox 1b (Prrx1b), one of major isoforms of Prrx1, has been identified as a new epithelial-mesenchymal transition (EMT) inducer. However, the function of Prrx1b in TNBC has not been elucidated. In this study, we found that Prrx1b was significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 29 publications
0
27
0
Order By: Relevance
“…After washing, biotin labeled secondary antibody against rabbit immunoglobulin was applied for 30 min at room temperature. The results were evaluated as described previously [12]. …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…After washing, biotin labeled secondary antibody against rabbit immunoglobulin was applied for 30 min at room temperature. The results were evaluated as described previously [12]. …”
Section: Methodsmentioning
confidence: 99%
“…After 42 days, the mice were killed, and the tumors were weighed. The tumor volumes were determined as described previously [12]. 2 × 10 6 cells were injected into the tail vein to establish a lung metastatic model of breast cancer (n=8).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As numerous genetic changes are in relation to cancer cell invasion and metastasis,14, 19, 20, 21, 22 great efforts have been made in the identification of novel key regulators and the potential mechanisms involved in this process over the years. Interestingly, recent studies have revealed that CRYAB is aberrantly overexpressed in various types of cancer, and its expression could promote cell invasion and metastasis 8, 9, 10.…”
Section: Discussionmentioning
confidence: 99%
“…EMT is a biological process that allows a polarized epithelial cell, which normally interacts with the basement membrane via its basal surface, to undergo multiple biochemical changes that enable it to assume a mesenchymal cell phenotype, which includes enhanced migratory and invasive capacities (10). Studies have reported that Wnt/β-catenin is among the main pathways that regulate EMT, which may be the key mechanism that mediates breast cancer progression (11,12). Agents that target Wnt/β-catenin and downstream molecules such as survivin and cyclin D1 have a potent inhibitory effect on cell proliferation, invasion, and metastasis in…”
Section: Introductionmentioning
confidence: 99%